Methodological Challenges in Studies Comparing Prehospital Advanced Life Support with Basic Life Support. Issue 4 (3rd April 2017) - Li, Timmy; Jones, Courtney M. C.; Shah, Manish N.; Cushman, Jeremy T.; Jusko, Todd A.
Abstract: Determining the most appropriate level of care for patients in the prehospital setting during medical emergencies is essential. A large body of literature suggests that, compared with Basic Life Support (BLS) care, Advanced Life Support (ALS) care is not associated with increased patient survival or decreased mortality. The purpose of this special report is to synthesize the literature to identify common study design and analytic challenges in research studies that examine the effect of ALS, compared to BLS, on patient outcomes. The challenges discussed in this report include: (1) choice of outcome measure; (2) logistic regression modeling of common outcomes; (3) baseline differences between study groups (confounding); (4) inappropriate statistical adjustment; and (5) inclusion of patients who are no longer at risk for the outcome. These challenges may affect the results of studies, and thus, conclusions of studies regarding the effect of level of prehospital care on patient outcomes should require cautious interpretation. Specific alternatives for avoiding these challenges are presented. T Li, CMC Jones, MN Shah, JT Cushman, TA Jusko .Methodological challenges in studies comparing prehospital Advanced Life Support with Basic Life Support .Prehosp Disaster Med .2017 ;32 (4 ):444 –450 .